Association of Arterial Stiffness (Brachial–Ankle Pulse Wave Velocity) with Angiographic Outcomes After Drug-Eluting Stent Implantation: A Retrospective Lesion-Level Cohort Study - Hangyeol Kim; Hyun Sung Joh; Woo-Hyun Lim; Hack-Lyoung Kim; Sang-Hyun Kim; Jae-Bin Seo (Journal of Clinical Medicine, 2026)
Background/Objectives: Elevated brachial–ankle pulse wave velocity (baPWV) predicts adverse outcomes after percutaneous coronary intervention, but its relation to the quantitative angiographic outcomes of drug-eluting stent (DES) implantation is unknown. We examined baPWV against acute gain and late lumen loss. Methods: In a retrospective single-center cohort, 242 lesions in 141 patients with paired quantitative coronary angiography (QCA) were analyzed. baPWV was modeled per 1 SD with patient-level clustering (linear mixed model for acute gain; cluster-robust ordinary least squares for late lumen loss), with a Bonferroni-corrected α = 0.025 for the co-primary outcomes. Generalizability was assessed against registry patients without QCA. Results: An unadjusted inverse association with acute gain (β = −0.093 mm per 1 SD; p = 0.013) was fully attenuated after adjustment (β = −0.019; 95% CI −0.106 to +0.068; p = 0.67). baPWV was not associated with late lumen loss (adjusted β = −0.021; 95% CI −0.091 to +0.050; p = 0.57). Conclusions: Pre-procedural baPWV showed no independent association with acute gain or late lumen loss after DES implantation, consistent with a marker of systemic cardiovascular risk rather than independent local angiographic information. These data do not support using baPWV to guide procedural decisions.